SISTEM DETEKSI KERUSAKAN BEARING RODA PADA MOBIL MENGGUNAKAN SENSOR PIEZOELECTRIK BERBASIS ANDROID - M Cecep Zaelani (Ilmu Komputer, FMIPA, Universitas Pakuan, 2019)
Bearing damage to the car's wheels has prompted several studies to create a system capable of detecting damage to the wheel bearings. To overcome this problem, a wheel bearing damage detection system has been built and tested using a piezoelectric sensor. The results showed that piezoelectric sensors detect bearing damage to the wheels based on their frequency, which is 0 - 5 Hz is good, 6-30 Hz is not good, and 31 - 355 Hz is badly damaged. Data can be displayed in realtime via Android. The results of this study can be used at dealers or car repair centers.